IMPLEMENTASI PELAKSANAAN PROYEK PENGUATAN PROFIL SISWA PANCASILA DAN PROFIL SISWA RAHMATAN LIL ALAMIN (P5-P2RA) DI SMK AL-HUDA WONOGIRI - Salsabila, Esa Shofa Kamila (Jurnal Jaringan Penelitian Pengembangan Penerapan Inovasi Pendidikan (Jarlitbang), 2025)
This study examines the implementation of the Pancasila Student Profile Strengthening Project and Rahmatan Lil Alamin Student Profile (P5-P2RA) in the context of vocational education. The Pancasila Student Profile consists of six main dimensions: faith and devotion to the Almighty God, global diversity, cooperation, independence, critical reasoning, and creativity. Meanwhile, the Rahmatan Lil Alamin Student Profile encompasses five dimensions of morality: towards Allah SWT, fellow humans, nature, oneself, and the nation and state. This research employs a qualitative approach with a case study method conducted at SMK Al Huda Wonogiri, Central Java. Data collection was carried out through participatory observation, in-depth interviews with the resourc., and documentation. Data analysis uses the Miles and Huberman model with stages of data reduction, data presentation, and conclusion drawing. The P5-P2RA concept aims to develop a generation that is not only academically excellent but also possesses strong character and noble ethics. The implementation of the Pancasila Student Profile Strengthening Project and Rahmatan Lil Alamin Student Profile (P5-P2RA) at SMK IT Al Huda Wonogiri represents a groundbreaking educational innovation that successfully harmonizes vocational training with comprehensive character development rooted in both Pancasila and Islamic values.